2020
DOI: 10.1017/s0952523820000097
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic photoreceptors: Mechanisms underlying changes in structure and function

Abstract: Based on clinical findings, diabetic retinopathy (DR) has traditionally been defined as a retinal microvasculopathy. Retinal neuronal dysfunction is now recognized as an early event in the diabetic retina before development of overt DR. While detrimental effects of diabetes on the survival and function of inner retinal cells, such as retinal ganglion cells and amacrine cells, are widely recognized, evidence that photoreceptors in the outer retina undergo early alterations in diabetes has emerged more recently.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 139 publications
1
4
0
Order By: Relevance
“…Both in patient and animal models, the detrimental influence of hyperglycemia on the inner retinal neuronal viability and function is described. Yet, the impact of hyperglycemia on photoreceptor function remains controversial [30][31][32][33]. In our study, we noted the impaired functions of Müller glia/bipolar cells and photoreceptors in 4-month diabetic rats, which is consistent with the observations of others [34][35][36][37].…”
Section: Discussionsupporting
confidence: 92%
“…Both in patient and animal models, the detrimental influence of hyperglycemia on the inner retinal neuronal viability and function is described. Yet, the impact of hyperglycemia on photoreceptor function remains controversial [30][31][32][33]. In our study, we noted the impaired functions of Müller glia/bipolar cells and photoreceptors in 4-month diabetic rats, which is consistent with the observations of others [34][35][36][37].…”
Section: Discussionsupporting
confidence: 92%
“…Nonetheless, the loss of photoreceptors in the human diabetic retina remains controversial. 22 There is a paucity of evidence demonstrating photoreceptor death in diabetic patients, although it is possible that S-cones may be selectively lost in patients with DR. 23 A previous cross-sectional study on 29 young adults and adolescents with type 1 diabetes and no DR found that these diabetic eyes had no significant difference in cone density on AO imaging compared with healthy controls. 24 In another study by Zaleska-Żmijewska et al, 11 cone density at 2° eccentricities was significantly lower in eyes with mild and moderate NPDR compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…This reduces oxygen reserve in photoreceptors, and even a minor disruption of oxygen flow in diabetes can result in severe hypoxia. The creation of acellular capillaries, capillary blockage, and capillary dropout can contribute to retinal hypoxia, hence, the vascular pathology of DR [3].…”
Section: Discussionmentioning
confidence: 99%
“…The loss of photoreceptors in the diabetic retina is still debatable, and various optical coherence tomography (OCT) studies in diabetic patients show that the thickness of the inner retina, including the nerve fiber, retinal ganglion cell, and inner plexiform layers, decreases with the duration of diabetes [3]. In a diabetic animal model study, the outer nuclear layer thickness is frequently reduced, specifically in models of type 1 disease with early-onset.…”
Section: Discussionmentioning
confidence: 99%